Helping Families Make Difficult Choices: Creation and Implementation of a Decision Aid for Neuromuscular Scoliosis Surgery. Issue 8 (December 2015) - Shirley, Eric; Bejarano, Carolina; Clay, Catharine; Fuzzell, Lindsay; Leonard, Sharon; Wysocki, Tim
Abstract : Background: Decision aids serve to prepare families for a meaningful discussion with their physician during the shared decision-making (SDM) process. Although SDM processes have been used primarily in adult health care settings, we sought to develop a decision aid for use in pediatrics. The treatment of neuromuscular scoliosis was selected due to the complexity of decision making when surgery is considered. Our objective was to determine whether this tool would improve families' knowledge and satisfaction while decreasing decisional conflict. Methods: The decision aid was created using a multistep process to provide unbiased evidence-based information about the risks and benefits of the treatment options for neuromuscular scoliosis. The initial draft was written by an orthopaedic surgeon and then formatted by a multidisciplinary group to meet international decision aid standards. The document underwent local, national, and international peer review before prospective implementation by 4 orthopaedic surgeons at a single institution. The decision aid was evaluated and revised for further use. Results: Eleven children, mean age 12 years (range, 8 to 17 y), were included in the study. Nine of the 11 families opted for surgery. The mean scores on the knowledge test increased from 3.0 (range, 2 to 5) to 4.0 (range, 3 to 5) of a possible 5 points ( P =0.067). The mean item score on the SDM satisfaction scale was 3.8 (range, 3.5 to 4.0). The mean score on the SURE test for decisional conflict was 3.7 (range, 3 to 4) of a maximum score of 4. The mean total score on the clinician SDM satisfaction scale was 22.5 (range, 17 to 25). Conclusions: The decision aid created for this complex decision resulted in improvements in knowledge gain, satisfaction, and decisional conflict while gaining acceptance of the physicians who utilized it. Consideration should be given to developing additional decision aids within professional societies to maximize efficiency and consensus. Level of Evidence: Level II—decision analysis.